دور علماء الإسلام في مواجهة التحديات بين المسلمين في الصين (The Role of The Islamic Scholars In Encountering The Challenges Among The Muslims In China) - الصيني يونس عبد الله ما تشنغ بين (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
الملخّص إن بقاء الإسلام، ورغبة المسلمين في الحفاظ على عقيدة الإسلام، وشريعته السمحاء في الصين راجعة إلى جهود علمائنا الأجلاء الذين نَهَلُوا العلم الصافي من مَعِينِ القرآن والسنة. وخدمتهم من خلال ترجمة معاني القرآن الكريم، وتبسيط العقيدة والشريعة باللغة الصينية خير دليل على ذلك. ويحاول الباحث تسليط الضوء من خلال هذا البحث على طبيعة الإسلام في أرض الصين، كاشفا أمر وضع الإسلام وطبيعة حال المسلمين، وتحدياتهم قديما وحديثا، مبينا محاولتهم على حفاظ دين الإسلام، وأداء شعائره. ويؤمن الباحث من خلال توصيف حالة الإسلام والمسلمين، أن صلاح المسلمين، وبقاءهم كأمة مسالمة لا رغبة لها؛ إلا في الإصلاح، والتعمير في الأرض، فهو لا يتحقق إلا بإصلاح النفس، وعودتها إلى طاعة الله سرا وعلانية دون الإنغماس في تحقيق الرغبات المادية، وإشباع المطامع الشهوانية من خلال جمع حطام الدنيا دون الالتفات إلى حلال وحرام، وطاعة ومعصية. الكلمات المفتاحيّة: جهود العلماء، ثقافة الإسلام، مصادر الإسلام الأصلية، التحديات، الصين، الدعوة. Abstract The continuation of Islam in China and the aspiration of the Muslims to maintain Islamic faith and its true tolerant legal system retract to the struggles of our respected scholars who learnt the knowledge of the Qurʼan and the Prophetic traditions (al-Sunnah). The services they rendered in translating the meaning of the Qurʼan, simplifying the creed and the legal system of Islam into Chinese language are good indications in that context. In this paper, the researcher is trying to highlight the normal nature of Islam in China by exploring the position and nature of the Muslims, their contemporary and past challenges, and revealing their attempts to preserve the religion of Islam in discharging the religious rites. Through the depiction of Islam and the Muslims, the researcher believes that the wellbeing of Muslims and their continuous survival to be a peace-loving nation could not be achieved without the reform and proper development through self-reformation and its return to full submission to Allah both in private and public life, and without indulging in attainment of material desires and satiating the lust of accumulating ephemeral materials of this world without paying any heed to lawfulness or unlawfulness, or to being obedient or disobedient. Keywords: Effort of the Scholars, Islamic Culture, Noble Origin of Islam, Challenges, Propagation of the Religion.